Polyelectrolyte/surfactant films spread from neutral aggregates. Issue 24 (25th May 2016) - Campbell, Richard A.; Tummino, Andrea; Noskov, Boris A.; Varga, Imre
Abstract : We describe a new methodology to prepare loaded polyelectrolyte/surfactant films at the air/water interface by exploiting Marangoni spreading resulting from the dynamic dissociation of hydrophobic neutral aggregates dispensed from an aqueous dispersion. Abstract : We describe a new methodology to prepare loaded polyelectrolyte/surfactant films at the air/water interface by exploiting Marangoni spreading resulting from the dynamic dissociation of hydrophobic neutral aggregates dispensed from an aqueous dispersion. The system studied is mixtures of poly(sodium styrene sulfonate) with dodecyl trimethylammonium bromide. Our approach results in the interfacial confinement of more than one third of the macromolecules in the system even though they are not even surface-active without the surfactant. The interfacial stoichiometry of the films was resolved during measurements of surface pressure isotherms in situ for the first time using a new implementation of neutron reflectometry. The interfacial coverage is determined by the minimum surface area reached when the films are compressed beyond a single complete surface layer. The films exhibit linear ripples on a length scale of hundreds of micrometers during the squeezing out of material, after which they behave as perfectly insoluble membranes with consistent stoichiometric charge binding. We discuss our findings in terms of scope for the preparation of loaded membranes for encapsulation applications and in deposition-based technologies.